Synthesis and Characterization of Tri-Composite Activated Carbon - Ahmedzeki, Nada S.; Ali, Salah M.; Al-Karkhi, Sarah R. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Activated carbon loading with metals oxides is new adsorbents and catalyst, which seem very promising for desulfurization process. The present study deals with the preparation of three metals oxides loaded on activated carbon (AC). The tri composite of ZnO/NiO/CoO/AC was characterized by X-Ray Diffraction (XRD), X-Ray florescence (XRF), N2 adsorption for BET surface area, pore volume and Atomic Force Microscopy (AFM). The effect of calcination temperature is investigated. The best calcination temperature is 250oC based on the presence of phase, low weight loss and keep at high surface area. The surface area and pore volume of prepared tri composite are 932.97m2/g and 0.6031cm3/g respectively. The average particle size of tri-composite is 104.72 nm. Results confirmed a successful route for preparing the composite with promising characteristics.